Implementasi Manajemen Sumber Daya Manusia Dalam Meningkatkan Efektivitas Madrasah (Studi Kasus Pada MI Tahfidz Madinatul Huffadz Ngawi ) - Hadi, Samsul (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
This study aims to analyze the implementation and effectiveness of human resource management (HRM) within the context of Islamic educational institutions. Employing a qualitative descriptive approach, data were collected through interviews and documentation, and validated using source triangulation. Informants included the head of the madrasah, the head of administration, and teachers. Findings from MI Tahfidz Madinatul Huffadz Ngawi indicate that HRM has been effectively implemented across four key aspects: recruitment, training, compensation, and termination, aligning with Schuler's theory. The results are expected to contribute to the development of HRM theory and practice in educational institutions.